High‐latitude ionospheric equivalent currents during strong space storms: Regional perspective. Issue 1 (15th January 2015) - Juusola, L.; Viljanen, A.; van de Kamp, M.; Tanskanen, E. I.; Vanhamäki, H.; Partamies, N.; Kauristie, K.
Abstract Geomagnetically induced currents (GIC) are a space weather phenomenon that can interfere with power transmission and even cause blackouts. The primary drivers of GIC can be represented as ionospheric equivalent currents. We used International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer data from 1994–2013 to analyze the extreme behavior of the time derivative of the equivalent current density (|ΔJeq|/Δt) together with the occurrence of modeled GIC in the European high‐voltage power grids (1996–2008). Typically, when intense |ΔJeq|/Δt occurred, geomagnetic activity extended to latitudes <60°, Kp ≥ 8, and modeling suggested large GIC in the European high‐voltage power grids. Intense, although short‐lived, |ΔJeq|/Δt also occurred when geomagnetic activity was confined to latitudes >60°. In such cases, typically 5≤Kp<8, and modeling suggested that there were no large GIC in the European high‐voltage power grids. Intense |ΔJeq|/Δt and GIC occurred preferentially before midnight or at dawn and were rare after noon. There was a seasonal peak in October and a minimum around midsummer. Intense |ΔJeq|/Δt and GIC occurred preferentially in the declining phase of the solar cycle and were rare around solar minima. A longer perspective (1975–2013) was obtained by comparison with the time derivative of the magnetic field from the IMAGE station Nurmijärvi (NUR, MLAT ∼57°). NUR data indicated that the quietness of summer months may have been due to a coincidental lack of intense storms during the shorter period. NUR data agreed with the increased activity in the declining phase but demonstrated that extreme events could also occur during solar minima.